Enhanced resting‐state dynamics of the hemoglobin signal as a novel biomarker for detection of breast cancer - Graber, Harry L.; Al abdi, Rabah; Xu, Yong; Asarian, Armand P.; Pappas, Peter J.; Dresner, Lisa; Patel, Naresh; Jagarlamundi, Kuppuswamy; Solomon, William B.; Barbour, Randall L. (Medical physics (Lancaster), 2015)
Purpose: The work presented here demonstrates an application of diffuse optical tomography (DOT) to the problem of breast‐cancer diagnosis. The potential for using spatial and temporal variability measures of the hemoglobin signal to identify useful biomarkers was studied. Methods: DOT imaging data were collected using two instrumentation platforms the authors developed, which were suitable for exploring tissue dynamics while performing a simultaneous bilateral exam. For each component of the hemoglobin signal (e.g., total, oxygenated), the image time series was reduced to eight scalar metrics that were affected by one or more dynamic properties of the breast microvasculature (e.g., average amplitude, amplitude heterogeneity, strength of spatial coordination). Receiver‐operator characteristic (ROC) analyses, comparing groups of subjects with breast cancer to various control groups (i.e., all noncancer subjects, only those with diagnosed benign breast pathology, and only those with no known breast pathology), were performed to evaluate the effect of cancer on the magnitudes of the metrics and of their interbreast differences and ratios. Results: For women with known breast cancer, simultaneous bilateral DOT breast measures reveal a marked increase in the resting‐state amplitude of the vasomotor response in the hemoglobin signal for the affected breast, compared to the contralateral, noncancer breast. Reconstructed 3D spatial maps of observed dynamics also show that this behavior extends well beyond the tumor border. In an effort to identify biomarkers that have the potential to support clinical aims, a group of scalar quantities extracted from the time series measures was systematically examined. This analysis showed that many of the quantities obtained by computing paired responses from the bilateral scans (e.g., interbreast differences, ratios) reveal statistically significant differences between the cancer‐positive and ‐negative subject groups, while the corresponding measures derived from individual breast scans do not. ROC analyses yield area‐under‐curve values in the 77%–87% range, depending on the metric, with sensitivity and specificity values ranging from 66% to 91%. An interesting result is the initially unexpected finding that the hemodynamic‐image metrics are only weakly dependent on the tumor burden, implying that the DOT technique employed is sensitive to tumor‐induced changes in the vascular dynamics of the surrounding breast tissue as well. Computational modeling studies serve to identify which properties of the vasomotor response (e.g., average amplitude, amplitude heterogeneity, and phase heterogeneity) principally determine the values of the metrics and their codependences. Findings from the modeling studies also serve to clarify the influence of spatial‐response heterogeneity and of system‐design limitations, and they reveal the impact that a complex dependence of metric values on the modeled behaviors has on the success in distinguishing between cancer‐positive and ‐negative subjects. Conclusions: The authors identified promising hemoglobin‐based biomarkers for breast cancer from measures of the resting‐state dynamics of the vascular bed. A notable feature of these biomarkers is that their spatial extent encompasses a large fraction of the breast volume, which is mainly independent of tumor size. Tumor‐induced induction of nitric oxide synthesis, a well‐established concomitant of many breast cancers, is offered as a plausible biological causal factor for the reported findings.